VARIABILITAS KEKUATAN KAYU PADA POHON MAHONI - Suparman Karnasudirdja (Jurnal Penelitian Hasil Hutan, 1985)
A  study  on a  variation of  bending  and compression  parallel to the grain strength  in Mahogany  (Swietenia mahogany) tree  has been  under  taken.  The material  consisted of 5  trees, each  of  which was represented by 4 bolt  taken  respectively from  near tree  base, at middle  half and  upper end of  the merchantable bole.  The test pieces  were then drawn from  each bolt  following   the  cruciform  pattern  of  the  ASTM   D14362 procedure. Using this pattern, 221  and  197  test specimens were respectively obtained  for  the  bending  and compression test.  The  result  shows  that  the  tree averages of  the  bending strength ranges from  90 - 110% of  the species  maan value, the cardinal point  averages from  100 -101% and the position within tree (bolt)  averages from  97 - 102%, As has been anticipated the tree averages are significantly different in both  the bending  and  compression strengths. Computation of the precision  of estimates  of the species  mean in term  of the probable limit  of  error (PLE) as percentage of  the species  mean  within 95%  confidence band as suggested by Pearson (1952)  indicates  an error of  9,51% and  12,44%   for  respectively the bending  and  compression   strength.  Values  of  the probable limit of error PLE were then calculated  using various combination of number of test pieces per tree and number  of  trees,  and  the result  compared   with   those  obtained   from  previous test  using  Agathis lorantifolia and  Schima  wallichii  tree species.  It shows  that  for structural and  non-structural purposes at leat 10 trees per species,  and 5-10 specimens  per  tree should  be employed   in future  strength  test in order to obtain  an error of  between  5 -10%. This is definitely an advantage  compared with  the  current  procedure.